(untitled) (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To evaluate the effect of obesity on functional outcome of TKA in terms of range of motion and knee society score. Methods: This is a prospective observational study. We included 350 consecutive patients in whom simultaneous bilateral total knee arthroplasty was done due to knee osteoarthritis from April 2014 to June 2015 by a single surgeon in a single centre. Patients’ demographic data, weight, height, body mass index, preoperative range of motion and knee society score was taken from Pakistan National Joint Registry. Patients were divided into four groups according to BMI: (1) normal (2) overweight (3) obese and (4) severely obese. At 6 months, detailed assessment of the patients, which included range of motion and calculation of knee society score, was done. We evaluated the effect of obesity on functional outcome after TKR by comparing means and proportions of the outcome variables across these four groups. Results: At the follow-up after 6 months, we found similar improvement in range of motion and knee society scores in obese and non-obese patients. Conclusions: Obese patients should not be refrained from having TKA if indicated. The data reflects that after surgery, their mobility increases so they can reduce their weight as well as the chances of having associated morbidities. Key words: Total knee arthroplasty, Body mass index, obesity